Heterosubtypic T-Cell Immunity to Influenza in Humans: Challenges for Universal T-Cell Influenza Vaccines - Sridhar, Saranya (Frontiers in Immunology, 2016)
Influenza A virus (IAV) remains a significant global health issue causing annual epidemics, pandemics and sporadic human infections with highly pathogenic avian or swine influenza viruses. Current inactivated and live vaccines are the mainstay of the public health response to influenza although vaccine efficacy is lower against antigenically distinct viral strains. The first pandemic of the 21st century underlined the urgent need to develop new vaccines capable of protection against a broad range of influenza strains. Such “universal” influenza vaccines are based on the idea of heterosubtypic immunity wherein immune responses to epitopes conserved across IAV strains can confer protection against subsequent infection and disease. T-cells recognising conserved antigens are a key contributor to reducing viral load and limiting disease severity during heterosubtypic infection in animal models. Recent studies undertaken during the 2009 H1N1 pandemic provided key insights into the role of cross-reactive T-cells in mediating heterosubtypic protection in humans. This review focuses on human influenza to discuss the epidemiological observations that underpin cross-protective immunity, the role of T-cells as key players in mediating heterosubtypic immunity including recent data from natural history cohort studies and the ongoing clinical development of T-cell inducing universal influenza vaccines. The challenges and knowledge gaps for developing vaccines to generate long-lived protective T-cell responses is discussed.